FRI0589 A joint procedural recommendation on fdg-pet/ct(A) imaging in large vessel vasculitis and polymyalgia rheumatica from the cardiovascular and inflammation & infection committees of the eanm, the cardiovascular council of the snmmi, the pet interest group (PIG), and endorsed by the asnc. (12th June 2018) - Slart, R.
Abstract : Background: [18F]-fluorodeoxyglucose positron emission tomography combined with anatomical computed tomography angiography, (FDG-PET/CTA) is increasingly used in Large Vessel Vasculitis (LVV, consisting of Giant Cell Arteritis (GCA) and Takayasu Arteritis (TA)) and Polymyalgia Rheumatica (PMR), and may be of value for optimal diagnosis, disease activity monitoring, and evaluation of damage development. There are currently no general accepted procedural guidelines regarding PET imaging acquisition for LVV and PMR. Objectives: The aim of our study is to provide recommendations and statements, based on the available evidence in the literature combined with consensus of experts in the field, for patient preparation, FDG-PET/CT(A) acquisition and interpretation. Methods: A systematic literature review was conducted to retrieve data on FDG-PET/CT(A) imaging in LVV and PMR. Expert consensus was used to propose recommendations in the absence of sufficiently robust data. Levels of evidence and grades of recommendations were attributed to the statements of different indications according to published criteria. Results: Based on the literature review combined with expert consensus recommendations and statements that could be formulated: see table 1. Conclusions: This joint recommendation highlights that standardisation and general consensus regarding the optimal procedural performance of FDG-PET/CT(A) imaging in LVV and PMR are highly needed. Some recommendations and statements could be formulated however, there are also a lot of open issues which need to be studied for optimal performance of FDG-PET/CT(A) in the diagnosis, (treatment)monitoring and future theranostics in LVV/PMR to increase the levels of evidence and improve the grades of the recommendations. Disclosure of Interest: None declared